The effect of thiamine, biotin, and pyridoxine on the interaction dynamics of wine yeast consortia - Van Goeverden, Hannah Isabel (Stellenbosch : Stellenbosch University, 2025)
Van Goeverden, Hannah Isabel. 2024. The effect of thiamine, biotin, and pyridoxine on the interaction dynamics of wine yeast consortia. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131955